2010
DOI: 10.1126/science.1190672
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptable Peptide-Based Porous Material

Abstract: Porous materials find widespread application in storage, separation, and catalytic technologies. We report a crystalline porous solid with adaptable porosity, in which a simple dipeptide linker is arranged in a regular array by coordination to metal centers. Experiments reinforced by molecular dynamics simulations showed that low-energy torsions and displacements of the peptides enabled the available pore volume to evolve smoothly from zero as the guest loading increased. The observed cooperative feedback in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
278
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(292 citation statements)
references
References 32 publications
9
278
0
1
Order By: Relevance
“…The silver ion concentration in supernatant solution was determined by cathodic stripping voltammetry. It was shown that materials (1) (Ag3(4-PO3-C6H4-COO), which exhibited the more compact structure released only traces of silver ions in solution while materials (2) (Ag (4-PO3H-C6H4-COOH) and (3) (Ag(3-PO3H -C6H4-COOH)), characterized by the presence of free carboxylic acid functional 19 groups in their structure, released more easily silver salts in water. These results, concomitantly with the silver release capacity of material (4) previously reported, clearly show that the silver release is dictated by the topology of the hybrid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The silver ion concentration in supernatant solution was determined by cathodic stripping voltammetry. It was shown that materials (1) (Ag3(4-PO3-C6H4-COO), which exhibited the more compact structure released only traces of silver ions in solution while materials (2) (Ag (4-PO3H-C6H4-COOH) and (3) (Ag(3-PO3H -C6H4-COOH)), characterized by the presence of free carboxylic acid functional 19 groups in their structure, released more easily silver salts in water. These results, concomitantly with the silver release capacity of material (4) previously reported, clearly show that the silver release is dictated by the topology of the hybrid.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the drug, or pro-drug, (e.g. peptide, 19 nicotinic acid 20 ) must possess a reactive functional groupity (e.g. carboxylate) that can interact with the inorganic network that is generated during the formation of the hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, remarkable progress has been made in this regard in the development of metal-organic materials (MOMs), such as metal-organic frameworks (MOFs) 5,6 and metal-organic polyhedra (MOPs) 7 , assembled from molecular building units. These materials possess unique properties and vast application potential [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . The hallmark of these new materials is their modular design, which is far beyond the scope of other porous materials 22,[25][26][27][28][29][30][31][32][33][34][35][36] and allows for facile structure and property tuning.…”
mentioning
confidence: 99%
“…Sorbents examined for fluorocarbon-based adsorption chillers have thus far been limited to activated carbon 7,8 and zeolites 9 . Although the literature on gas adsorption in MOFs is very extensive [10][11][12][13][14][15][16][17][18][19] , fluorocarbon adsorption has been limited to zeolites and activated carbons [7][8][9] . The adsorption behaviour of the MOFs with high capacity at very low vapor pressures suggests MOFs can, in principle, be used in fluorocarbon-based adsorption heat pumps, separation of fluorocarbons from azeotrope mixture, removal of environmentally hazardous gases from atmosphere.…”
mentioning
confidence: 99%